If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = x Reorder the terms: 2(4 + x) = x (4 * 2 + x * 2) = x (8 + 2x) = x Solving 8 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 8 + 1x = x + -1x Combine like terms: x + -1x = 0 8 + 1x = 0 Add '-8' to each side of the equation. 8 + -8 + 1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 0 + -8 1x = 0 + -8 Combine like terms: 0 + -8 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 3*(250-x)=250+x | | -6x+8=58-x | | 9x^2+9x+9=0 | | 24m^2+18m-15=0 | | (6-2)(5-8)= | | 6x-6=7(x-9) | | 4x+2=9-(9x-9) | | x^2-9x=1 | | 3x+4(2x-1)= | | 0.8x-0.6(4-x)=5.3 | | 6a-3(a+2)= | | 1x-10+x-5x+1=14+3x-8-1 | | 4xy-5y+2=0 | | -2x=3(x-5)+6 | | 3x-10=-4x+22 | | 3p(p-1)=18 | | 7x=50-1 | | 3(-8)+[6(-2)]= | | 3n^3-4n^2+n=0 | | 3(-8)+[16(-2)]= | | -5(4x+5)=4+2(4x-8) | | n^2+2n+24=0 | | 3(2z+7)+4=5(z-3) | | 1=3x-21 | | (y^2+2y)+(3y^2+4y+2)=0 | | 7(x+1)=6-2(7x+7) | | x^2=6x+10 | | 3X+3=2X+2 | | 9+6x+4-x=16+7-5 | | k=LMN | | 50x+20(x+6)+10(x+6)+5*2*(x+6)=1140 | | 13-4=-6x+17 |